Impact of Type 2 Diabetes Mellitus on Survival in Head and Neck Squamous Cell Carcinoma. (October 2017) - Foreman, Andrew; Lee, Daniel J.; McMullen, Caitlin; de Almeida, John; Muhanna, Nidal; Gama, Ricardo Ribeiro; Giuliani, Meredith; Liu, Geoffrey; Bratman, Scott V.; Huang, Shao Hui; O'Sullivan, Brian; Song, Yuyao; et al.
Objective: To identify any association between type 2 diabetes mellitus (T2DM) and survival outcomes for mucosal squamous cell carcinoma of the head and neck. An association has been demonstrated between T2DM and cancer outcomes at numerous sites, but data for the head and neck are limited. Improving our understanding of the impact that diabetes has on head and neck cancer survival is relevant for making treatment decisions and counseling patients regarding prognosis. Study Design: Retrospective cohort study. Setting: Academic tertiary referral head and neck cancer center. Subjects and Methods: By accessing data retrospectively from prospectively collected databases at the Princess Margaret Cancer Centre, patients were studied who were treated for mucosal head and neck squamous cell cancer between January 2005 and December 2011. Collection of clinical, pathologic, and survival data was completed with an emphasis on T2DM. Results: Of 2498 patients identified in the study period, 319 (12.8%) had T2DM. Five-year overall survival was not different between the diabetic (64%, 95% CI = 58%-71%) and nondiabetic (67%, 95% CI = 65%-69%; P = .078) groups. Furthermore, cause-specific survival did not demonstrate a statistically significant difference between groups (diabetic: 84%, 95% CI = 79%-88%, vs nondiabetic: 84%, 95% CI = 82%-86%; P = .67). Conclusion: Despite contradictory evidence at other cancer sites, the presence of T2DM alone does not appear to adversely affect cancer survival outcomes in head and neck squamous cell cancer. This is encouraging for the diabetic patients with head and neck squamous cell cancer, and it provides guidance for the multidisciplinary team that treats them.